High yielding Rainfed upland rice variety, CRAM 2 (ARICA 15) released for upland production systems in Cote d'Ivoire - CGIAR Research Program on Rice (2021)
CRAM 2 (ARICA 15), a rainfed upland rice variety with a high milling recovery, was released in Cote d'Ivoire in 2021.